Deterrent Effects of Clary Sage Oil and Two Major Constituents against Drosophila suzukii (Diptera: Drosophilidae) - Yu Wang; Fengyi Wen; Xiangyi Zhou; Guoxing Chen; Chunxia Tian; Jiali Qian; Huiming Wu; Mengli Chen (Insects)
Drosophila suzukii (Diptera: Drosophilidae), spotted-wing drosophila, poses a significant threat to soft-skinned fruit crops in the Americas, Europe, Africa, and Oceania, as well as in Asia. The application of chemical insecticides is the primary control strategy for D. suzukii; however, resistance has developed with the indiscriminate use of chemical insecticides. Essential oils, considered potential alternatives to pesticidal strategies, exhibit potent toxic and sublethal behavioral effects against numerous pests, including D. suzukii. Clary sage oil repels a variety of agricultural and household pests; however, whether it has a repellent effect against D. suzukii remains unknown. Here, we found that clary sage oil exhibited dose-dependent repellency against D. suzukii adults in a T-maze assay, a two-choice assay and a two-choice attraction assay. Also, clary sage oil showed a significant repellent effect against D. suzukii larvae. Next, we explored the chemical constituents of clary sage oil by GC-MS and identified two major constituents, linalyl acetate (40.03%) and linalool (23.02%). Furthermore, the behavioral assays of linalyl acetate and linalool showed that both compounds conferred comparable repellency against D. suzukii adults and larvae. Finally, we found clary sage oil, linalyl acetate, and linalool elicited EAG responses in D. suzukii, especially clary sage oil, suggesting the repellency was mediated by the olfactory system. These findings indicate that D. suzukii shows olfactory-based behavioral avoidance of clary sage oil, linalyl acetate, and linalool. Clary sage oil and its major constituents may be possible alternatives in the management of D. suzukii.